2021
DOI: 10.3390/nano11092169
|View full text |Cite
|
Sign up to set email alerts
|

Photoinitiated Polymerization of Hydrogels by Graphene Quantum Dots

Abstract: As a smart stimulus-responsive material, hydrogel has been investigated extensively in many research fields. However, its mechanical brittleness and low strength have mattered, and conventional photoinitiators used during the polymerization steps exhibit high toxicity, which limits the use of hydrogels in the field of biomedical applications. Here, we address the dual functions of graphene quantum dots (GQDs), one to trigger the synthesis of hydrogel as photoinitiators and the other to improve the mechanical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 61 publications
0
7
0
2
Order By: Relevance
“…Park et al (2022) investigated the design and manufacture of three types of hybrid poly(NIPAAm-co-BBVIm) (pNIBBIm) and CTS hydrogels with incorporated CNTs for smart drug delivery systems, with remarkable thermal and electrical responsive properties that enabled the development of an excellent controllable and switchable drug delivery platform for biomedical approaches [ 254 ]. Kim et al (2021) synthesized chemically flexible and mechanically tough PAA hydrogels using GQDs as a photo-initiator and confirmed that the unique photochemical properties of GQDs triggered the efficient cross-linking process of acrylamide monomers, enhancing their mechanical resistance and swelling behavior [ 255 ]. Finally, Mamidi et al synthesized carbon nano-onions to reinforce ultra-high molecular weight polyethylene (UHMWPE) [ 256 ] and gelatin hydrogels [ 257 , 258 ].…”
Section: Hybrid Hydrogel Compositesmentioning
confidence: 99%
“…Park et al (2022) investigated the design and manufacture of three types of hybrid poly(NIPAAm-co-BBVIm) (pNIBBIm) and CTS hydrogels with incorporated CNTs for smart drug delivery systems, with remarkable thermal and electrical responsive properties that enabled the development of an excellent controllable and switchable drug delivery platform for biomedical approaches [ 254 ]. Kim et al (2021) synthesized chemically flexible and mechanically tough PAA hydrogels using GQDs as a photo-initiator and confirmed that the unique photochemical properties of GQDs triggered the efficient cross-linking process of acrylamide monomers, enhancing their mechanical resistance and swelling behavior [ 255 ]. Finally, Mamidi et al synthesized carbon nano-onions to reinforce ultra-high molecular weight polyethylene (UHMWPE) [ 256 ] and gelatin hydrogels [ 257 , 258 ].…”
Section: Hybrid Hydrogel Compositesmentioning
confidence: 99%
“…Graphene quantum dots (GQDs), which are non-toxic and have a broad spectral absorption range, are ideal photo-initiators. Kim et al proposed the preparation of polyamide hydrogels using GQDs as a photo-initiator [ 62 ]. Their elastic modulus was 50 times higher and the swelling ratio was similar to that of conventional photo-initiated hydrogels.…”
Section: Preparation Methods Of Smart Hydrogelsmentioning
confidence: 99%
“…[83,141,142,[148][149][150][151][152][153][154][155][156][157][158][159][160][161][162] Verschiedene Kohlenstoff-basierte Strukturen mit intrinsischen Photoinitiierungseigenschaften wurden entwickelt. [34,35,41,83,130,138,141,142,146,147,[163][164][165][166][167][168][169][170][171][172] Diese photoinitiierenden Systeme sind erfolgreich für die traditionelle freie radikalische Polymerisation, die photo-ATRP, die photo-RAFT und die kationische Photopolymerisation eingesetzt worden. [34,41,142,163,173] Kohlenstoffnanomaterialien können auf unterschiedlichen Substraten beschichtet werden.…”
Section: Lichtempfindliche Heterogene Materialien: Ein Alternativer Wegunclassified